ONCE AGAIN ’T ’ḤD ŠBṬY YŚR’L IN II SAMUEL 7:7 - Murray, Donald (1987)
In the face of objections to existing attempts to resolve the puzzle of 't' hd šbty yśr' l in II Samuel 7:7, the reading 't' hd mkl šbty yśr'l is proposed, and justified textually on the grounds of usage elsewhere in the O.T., and exegetically in terms of its consonance with the polemical thrust of the text as a whole. Devant les objections auxquelles se heurtent les tentatives de solution de l'énigme: 't' hd šbty yśr'l de 2 Samuel 7,7, on propose de lire: 't' hd mkl, šbty yśr'l On justifie cette lecture: textuellement, d'après l'usage vétérotestamentaire; exégétiquement, en montrant qu'elle s'accorde avec la visée polémique du texte dans son ensemble.